Automated DD-path Testing and its Significance in SDLC Phases - Sattar, H.; Bajwa, I.S.; Shafi, U.F. (Journal of Digital Information Management, 2015)

NL2 Alloy: A tool to generate alloy from NL constraints - Bajwa, I.S.; Bordbar, B.; Lee, M.; Anastasakis, K. (Journal of Digital Information Management, 2012)
In this paper, we present a novel approach to generate Alloy code from Natural Language (NL) constraints. The proposed research is basically an extension of two projects, NL2OCL and UML2Alloy.Our method uses Natural Language Processing (NLP) and Model Transformation (MT) to transform constraints expressed in NL to Alloy. We do not directly transform NL to Alloy, instead we use multiple intermediate translations such as NL2SBVR and SBVR2OCL and finally OCL2Alloy. Such intermediate translations help us to monitor the whole process of translation and produce intermediate artifacts such as OCL constraints, which can be used for documentation purposes. and ensure that actual semantics of NL have been transformed to Alloy. The generated Alloy code can then be used to check if the original NL constraints are consistent. We also introduce the use of OMG's standard SBVR in translation of NL to formal languages. The NL2Alloy approach is also implemented as an Eclipse plugin.
Keywords: Alloy; Natural language; NL2OCL; SBVR; UML